Current perception and willingness towards organ donation and transplantation: A survey of undergraduate students at university of Malaya - Zanuddin, H.; Sern, T.J.; Zakaria, S.N.S. (Universiti Putra Malaysia, 2017)
The poor number of organ donation is becoming a very worrying phenomenon especially to those patients with chronic diseases, as well as those who require an immediate transplant. Although a variety of programmes and promotional campaigns have been organised and promoted by the agencies responsible for handling the organ donation, the number of donors is still at a discouraging level. Therefore, the objective of this study is to analyse the perceptions of young generation in regard to organ donation. Random samplings of 387 respondents consisting of undergraduate students at University of Malaya were selected for this study. The study found that young people's perceptions were very much influenced by their family members and friends, as well as family history. There is a significant difference between mean of gender and willingness towards organ donation and transplantation (t = -2.60, df = 385, p = <.05). The Spearman correlation shows a positive but weak correlation between the intention of the surveyed students towards registering as donors and their perceptions about organ donation and transplantation (r = .354, p <0.05). In sum, discussions on the issue of organ donation and transplantation should be held regularly in Higher Learning Institutions in order to change the misperceptions and misconceptions of the younger generation about organ donation and transplantation.